Developing a Dualistic Finance Model by Forming an Ecosystem of Islamic and Conventional Finance (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article explores the innovative concept of integrating Islamic and conventional finance within a dualistic ecosystem. Drawing on the principles of Sharia-compliant finance and traditional banking, this model seeks to create a harmonious financial environment that accommodates diverse investor preferences and fosters economic growth. The study employs a comprehensive literature analysis, detailing the theoretical foundations, methodologies, and potential outcomes of this dualistic finance model.